Sponge’s biodiversity in the limestone islands in Vietnam sea - Thung, Do Cong; Ngai, Nguyen Dang; Thuy, Le Thi (Vietnam Journal of Marine Science and Technology, 2020)
In 2017, 2018 and 2020, sponge samples were collected at 41 points in the waters surrounding Vietnam’s coastal limestone islands (Bai Tu Long, Ha Long bay, Cat Ba and Ba Lua archipelago). Research results have identified 54 species belonging to 33 genera, 24 families of Demosponge class distributed in this area. Ha Long bay area has the highest number of species (53 species), followed by Cat Ba (46 species), Bai Tu Long 19 species; Ba Lua archipelago (Kien Giang) has the least number of species (3 species). Sponges are concentrated in coral reefs with the highest number of species (48 species) and the lowest in the mud and sand bottom (4 species). Biomass of sponges varies from 0.2–1.5 kg/m2. There are 11 sites with high biomass, which have the potential to become Vietnam’s medicinal drug area.